Kansas forestry: condition and needs - Masters, Claud (My University, 1899)
Introduction: Much has been written on the subject of forestry, but very little that has been applied directly to the conditions and needs of our own state. The object of this thesis is to take up the conditions as we find them here, to see how they may be changed for the better, and what may be expected as a result. Present Conditions of the State One need be permitted to enjoy life in the state especially the western part, but a short time to be able to realize that this portion of the earth’s surface is greatly in need of more trees.
Citation: Masters, Claud. Kansas forestry: condition and needs. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Methods of Operation; Benefits as a Result; Theses; Manuscripts (documents)